Analisis Saldo Kas Optimal Badan Layanan Umum: Studi Kasus pada Rumah Sakit Umum Pusat dr. Kariadi - Rolly Indra (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2017)
Cash has an important role for private or public organizations. Public service agencies are authorized to manage cash. There is a phenomenon of high cash ratio at Kariadi Hospital compared to that of other hospitals, which indicate that cash balance management has not been effective. This study aims to analyze the optimal cash balances and analyze the causes of ineffective management of cash balances at Kariadi Hospital. The Optimal cash balance is analyzed using Miller and Orr methods. The ineffective management of cash balances is analyzed using factors to be considered when managing cash balances.In addition, the management of cash balances at Kariadi Hospital is compared to Sardjito Hospital (as benchmark) in order to analyze the differences. Factors, that are compared, are management’s policies and the management of cash balances, the contribution of the supervisory board and internal auditing unit, as well as the use of information technology. The results showed that the real cash balances in year 2016 were much higher than the optimal cash balances using the Miller-Orr model. factors to be considered, which caused the ineffevtive management of Kariadi Hospital’s cash balances, were the amount of cash balance outside the placement of time deposit that was not adjusted to the operational needs and cash forecastingand the policy of third party’s bill payment at the end of the year which caused the current liabilities declined and current ratio at the end of the year went up. Abstrak Kas mempunyai peranan penting bagi organisasi privat dan publik. Badan layanan umum diberikan wewenang untuk mengelola kas. Terdapat fenomena rasio kas yang tinggi pada RSUP dr. Kariadi dibandingkan RSUP lain yang mengindikasikan pengelolaan saldo kas belum efektif. Penelitian ini bertujuan menganalisis saldo kas optimal RS Kariadi dan penye bab pengelolaan saldo kas yang belum efektif. Saldo kas optimal dianalisis menggunakan metode Miller dan Orr. Pengelolaan saldo kas yang belum efektif dianalisis menggunakan faktor-faktor yang dinilai dapat memengaruhi pengelolaan saldo kas. Kemudian, membandingkan dan menganalisis perbedaan pengelolaan saldo kas RS Kariadi dengan RS Sardjito (sebagai benchmark). Faktor-faktor yang dibandingkan ialah kebijakan dan pengelolaan saldo kas oleh manajemen, kontribusi dewan pengawas, dan satuan pemeriksa internal serta penggunaan teknologi informasi. Hasil penelitian menunjukkan bahwa saldo kas riil tahun 2016 jauh lebih tinggi dibandingkan saldo kas optimal model Miller-Orr. Faktor penyebab pengelolaan saldo kas RS Kariadi tidak efektif ialah besaran saldo kas di luar deposito yang tidak disesuaikan dengan kebutuhan dan cash forecasting. Selain itu, kebijakan pembayaran tagihan kepada pihak ketiga pada akhir tahun menyebabkan kewajiban lancar menurun pada akhir tahun dan rasio lancar menjadi tinggi.